Health Management among Rural Women- A Case Study on the Current Health Status, Level of Awareness and Risk to Non-Communicable Diseases - Meenakshisundaram, K.S.; Vandhana, S. (International Journal of Psychosocial Rehabilitation, 2020)
Creating and increasing awareness on prevention of Non-Communicable Diseases (NCDs) among the rural women in India is a challenge, where social, economic, cultural and geographical factors contribute immensely to the livelihood and health of the rural women. NCD prevalence has gradually been increasing and health policy makers are apprehensive that selected NCDs might turn into an epidemic. A study was conducted to understand the current health status, level of awareness and risk of NCDs among the rural women of 23 villages in Nemili taluk in Vellore district, Tamilnadu. The study was done in two phases. Phase 1 study was to determine the current health status, NCD awareness and NCD risk of the women. Phase 2 study was to confirm the health status of the women based on diagnostic tests. In the first phase a validated questionnaire was used to collect data from randomly selected 48 respondents by survey method. The respondents were categorised into three age groups, 18-31 (Group 1), 32-48 (Group 2) and aged 49 years and above (Group 3). Using the data collected and analysing the results based on the risk factors like age, awareness, history and hereditary factors, the respondents were categorized into two clusters, high risk and relatively low risk respondents. Phase 1 study showed 93% of the respondents to be at high risk of NCD. In the second phase of the study , the respondents of the first phase were given a brief on the importance of diagnostic tests to understand their current health status and a closed questionnaire survey was done to know whether they were symptomatic to any of the selected NCDs, like Diabetes Hypertension, Cardio vascular disease, Kidney ailments, Breast and cervical cancer. After obtaining written consent, the respondents were subjected to diagnostic tests. Two laboratories that run quality control checks were chosen for conducting the tests. The test results were then analysed to confirm the respondent’s risk category based on risk factors like age, symptoms of illness, BMI, heart rate, Cholesterol, glucose and triglycerides level. Phase 2 study showed 73% of the respondents to be at high risk of NCD. The respondents were given the results of biochemical and physical tests and suitable diet charts. In addition, they were also provided with Breast cancer self- examination and cervical cancer guidelines. The data collected was analysed using SPSS software. It was found that 20% of respondents assessed to be in the high-risk group according to phase one study showed close to normal physical and biochemical values in the second phase. However, their age, level of awareness on NCDs, hereditary factors and previous history suggests that the respondents have to take the awareness initiatives and preventive healthcare concepts seriously, since they are at a potential risk of becoming high risk patients. Ingeniously initiatives like this will trigger health consciousness and the women will become receptive to preventive healthcare initiatives provided periodically by healthcare service providers. A positive response from the respondents is expected to set off preventive health awareness of NCDs in the community. It is recommended the reach of such health initiatives undertaken periodically by private, public and NGOs tends to gradually penetrate deeper and wider into the community..